Asuhan Keperawatan Gawat Darurat Hipoglikemia Pada Diabetes Melitus di RSUD Embung Fatimah Kota Batam - Setiadi Syarli; yulia devi putri; Yana Maulina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to identify to apply nursing care for hypoglycemia in diabetes mellitus with unstable blood sugar levels in the Emergency Installation of Embung Fatimah Hospital, Batam City Methods: This article with a case study design. The research was conducted by conducting interviews according to the format of nursing care and physical examinationResults: The results of the case study show that nursing care actions by providing dextrose or oral glucose therapy can increase blood sugar levels and reduce symptoms of hypoglycemiaConclusion: It is hoped that this research can be used as learning material and reference material in providing nursing care to clients with hypoglycemia